1967
DOI: 10.1128/jb.94.1.131-140.1967
|View full text |Cite
|
Sign up to set email alerts
|

Macromolecular Synthesis in Newly Transformed Cells of Bacillus subtilis

Abstract: The capacity of newly transformed cells of Bacillus subtilis to synthesize deoxyribonucleic acid (DNA), ribonucleic acid (RNA), and protein has been determined by folowing the kinetics of suicide after their exposure to tritiated precursors of each of these macromolecules. Competent cells, whether transformed or not, are heterogeneous with respect to DNA synthesis. About 40 to 50% are latent in DNA synthesis. This latency may persist for 2.5 to 3 hr since transformants are resistant to thymineless death for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
33
0

Year Published

1969
1969
2001
2001

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(37 citation statements)
references
References 35 publications
4
33
0
Order By: Relevance
“…Not only are cell division and elongation arrested, but DNA replication also appears to be blocked, as the nuclear bodies of competent cells retain the appearance of resting nucleoids. It has been reported that DNA replication and stable RNA synthesis are blocked in the presumptive competent cells during the development of competence (Dooley et al, 1971) and in newly transformed cells (McCarthy and Nester, 1967). The present results confirm that the inhibition of DNA replication continues during outgrowth.…”
Section: Discussionsupporting
confidence: 88%
“…Not only are cell division and elongation arrested, but DNA replication also appears to be blocked, as the nuclear bodies of competent cells retain the appearance of resting nucleoids. It has been reported that DNA replication and stable RNA synthesis are blocked in the presumptive competent cells during the development of competence (Dooley et al, 1971) and in newly transformed cells (McCarthy and Nester, 1967). The present results confirm that the inhibition of DNA replication continues during outgrowth.…”
Section: Discussionsupporting
confidence: 88%
“…The most suggestive comparison may be with a recent report that when the initiation of chromosome replication is specifically blocked in E. coli, cells become elongated, with centrally located nucleoids (Bernander et aL, 1995). mecA inactivation may be responsible for the DNA replication arrest of competent cells It has been shown that competent cells of B. subtilis are essentially inactive with respect to DNA replication (Dooley et aL, 1971;Dubnau and Cirigliano, 1973), and that chromosome replication in these cells is arrested at or near the replication terminus (McCarthy and Nester, 1967). Reversal of this block occurs with a delay, resulting in a prolonged lag before competent cells resume growth (McCarthy and Nester, 1967;Nester and Stocker, 1963).…”
Section: Inappropriate Comk Synthesis Causes An Abnormality In Nucleosupporting
confidence: 57%
“…mecA inactivation may be responsible for the DNA replication arrest of competent cells It has been shown that competent cells of B. subtilis are essentially inactive with respect to DNA replication (Dooley et aL, 1971;Dubnau and Cirigliano, 1973), and that chromosome replication in these cells is arrested at or near the replication terminus (McCarthy and Nester, 1967). Reversal of this block occurs with a delay, resulting in a prolonged lag before competent cells resume growth (McCarthy and Nester, 1967;Nester and Stocker, 1963). We have shown that the inactivation of mecA results in the loss of colony-forming ability and in a prolonged lag in the resumption of growth of the entire culture.…”
Section: Inappropriate Comk Synthesis Causes An Abnormality In Nucleomentioning
confidence: 99%
“…There may be two reasons for this. One is that competent cells are in a state of "biosynthetic latency" (31), in which DNA synthesis is drastically reduced compared with that in noncompetent cells (10,27). Postreplication repair must be considerably delayed in transformants relative to the beginming of excision repair, which should be able to begin as soon as the donor DNA is integrated.…”
Section: Discussionmentioning
confidence: 99%